2014
DOI: 10.1259/bjr.20140276
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of CT-guided transthoracic needle biopsy for the evaluation of the ground-glass opacity pulmonary lesions

Abstract: Objective: This meta-analysis is to determine the overall diagnostic yield of CT-guided transthoracic needle biopsy (TNB) of ground-glass opacity (GGO) lesions. Methods: A PubMed search was performed using "ground-glass opacity" crossed with "core biopsy" and "needle biopsy". Test performance characteristics with the use of forest plots, summary receiver operating characteristic curves and bivariate random effects models were summarized. Adverse events, if reported, were recorded. Results: Our search identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Several previously published systematic reviews or meta-analyses had been conducted with the purpose of obtaining the diagnostic values of conventional fluoroscopy, CT, ultrasonography (US), endoscopic ultrasound (EUS), and endobronchial ultrasound-guided (EBUS) PTNB for the diagnosis of pulmonary lesions [3841]. Lacasse et al reported that PTNB can be useful for the diagnosis of solitary or localized lesions in the lung [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previously published systematic reviews or meta-analyses had been conducted with the purpose of obtaining the diagnostic values of conventional fluoroscopy, CT, ultrasonography (US), endoscopic ultrasound (EUS), and endobronchial ultrasound-guided (EBUS) PTNB for the diagnosis of pulmonary lesions [3841]. Lacasse et al reported that PTNB can be useful for the diagnosis of solitary or localized lesions in the lung [38].…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al found that EBUS-guided PTNB was a cost-effective, safe and accurate modality for the staging of lung neoplasms,and the sensitivity of EBUS-guided PTNB can be enhanced by selecting patients with lymphadenopathy in CT or PET studies [40]. Yang et al stated that the CT-guided PTNB is a useful tool for the diagnosis and management of ground-glass opacity (GGO) lesions in the lung parenchyma [41]. However, all the four studies mentioned above either focused on the overall accuracy of PTNB or did not calculate the diagnostic accuracy values of CBCT-guided PTNB.…”
Section: Discussionmentioning
confidence: 99%
“…According to the guidelines of the American College of Chest Physicians,[ 5 ] the diagnostic yield of transthoracic needle biopsy for PPLs is at least 90%. Similarly, a recent meta-analysis demonstrated the validity of transthoracic needle biopsy for GGNs as well as solid lesions[ 6 ] although it was associated with a 29.8% risk of pneumothorax. Moreover, transthoracic needle biopsy carries serious risks of hemoptysis, hemothorax, tumor seeding, and air embolism.…”
mentioning
confidence: 99%
“…The main reason in support of this practice is a better understanding of the correlation between CT characteristics and histopathological findings (14-16), which has prompted surgical removal of these small GGNs on the basis of radiological diagnosis. Although a high specificity (0.94; 95% CI, 0.84-0.98) and sensitivity (0.92; 95% CI, 0.88-0.95) of percutaneous CT-guided biopsy for GGNs has been reported in meta-analyses (17,18), the diagnostic accuracy of small-sized (<1 cm) GGNs with a lower percentage of ground glass component tended to be lower, which made thoracic surgeons reluctant to perform preoperative biopsy for these small-sized GGNs. Additionally, the risk of complications, such as pneumothorax, hemoptysis and air embolism, is also a reason against biopsy.…”
Section: Role Of Preoperative Biopsies and Imaging Workupsmentioning
confidence: 99%